Financial management problems among enlisted personnel - Tiemeyer, Peter; Wardynski, Casey; Buddin, Richard J., 1951-; National Defense Research Institute (U.S.). Forces and Resources Policy Center; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 1999)
This documented briefing describes the financial well-being of enlisted military personnel. It provides evidence of the extent of personal financial problems in the military, describing how financial problems vary with the demographics of the military and with particular aspects of the military work environment. The study also examines which types of members receive financial assistance and what types of programs they use. The authors find that young enlisted personnel frequently experience significant financial management problems, which may stem in part from youthful irresponsibility and naivete. However, the military services must ensure that they are not contributing to members' financial problems in any way. Financial management classes currently being offered at some bases should be systematically evaluated to determine their effectiveness.
"National Defense Research Institute."
Includes bibliographical references (p. 23).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Soldiers -- United States -- Finance, Personal; United States -- Armed Forces -- Military life; United States -- Armed Forces -- Personnel management